A Tuscan Capital from Rusellae: Comparisons and Hypotheses (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
This paper presents the analysis of a heart-shaped Tuscan capital, avoid of context, found in Rusellae. Its shape allows to attribute it hypothetically to an arcaded structure identified with the Forum. Currently it is one of the few know evidences in Italy, where the heart-shaped pillar was not frequently used in Roman architecture. It also allows a better understanding of the restoration of the Forum during the Imperial era.
Keywords: Roselle; Rusellae; Tuscan order; Vitruvius; Forum; pillar; heart-shaped